2019
DOI: 10.7759/cureus.6348
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Anterior Lingual Depression in the Mandible: Cone Beam Computed Tomography Case Report and Review of the Literature

Abstract: The mandibular anterior lingual depression is an uncommon anatomical variant. It is difficult to be detected in conventional 2D plain radiographs representing a diagnostic challenge. In this report, we describe a patient who presented to the dental clinic for the extraction of impacted third molars. Upon cone beam computed tomography (CBCT) examination of the mandible, it was incidentally noted that he had bilateral anterior lingual depressions in his mandible. The presence of anterior lingual depressions is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Implant planning with conventional two-dimensional images such as periapical and panoramic radiographs has limitations such as distortion, magnifications, and superposition, which lead to inaccurate information [8][9][10][11][12] . The American Academy of Oral and Maxillofacial Radiology recommends the use of CBCT for preoperative implant evaluation and treatment planning This recommendation becomes even more important in the presence of limited bone amount, as seen in clinical evaluation 10,13,14 ABMD is clinically noticeable only during radiological examinations. Since the beam passes through less bone than the bone surrounding the depression site, its appearance appears to be a radiolucent area.…”
Section: Assessment Of the Radiographic Datamentioning
confidence: 99%
“…Implant planning with conventional two-dimensional images such as periapical and panoramic radiographs has limitations such as distortion, magnifications, and superposition, which lead to inaccurate information [8][9][10][11][12] . The American Academy of Oral and Maxillofacial Radiology recommends the use of CBCT for preoperative implant evaluation and treatment planning This recommendation becomes even more important in the presence of limited bone amount, as seen in clinical evaluation 10,13,14 ABMD is clinically noticeable only during radiological examinations. Since the beam passes through less bone than the bone surrounding the depression site, its appearance appears to be a radiolucent area.…”
Section: Assessment Of the Radiographic Datamentioning
confidence: 99%
“… 1 In previous reports, ABMDs in adult mandibles were found to have a depth of 1.5–4 mm, a width of 3–6 mm, and a length of 10–15 mm. 1 , 3 The anterior lingual mandibular depression (ALMD) is a lingual concavity that has been reported to occur in the anterior mandible 5 ; it has been compared to ABMD because they appear to be similar on periapical and panoramic radiographs as a result of superimposition. 1 However, no previous study has reported the occurrence of an ABMD and ALMD in the same mandible.…”
Section: Introductionmentioning
confidence: 99%